2009
DOI: 10.1126/science.1167375
|View full text |Cite
|
Sign up to set email alerts
|

Recombination of Retrotransposon and Exogenous RNA Virus Results in Nonretroviral cDNA Integration

Abstract: Retroviruses have the potential to acquire host cell-derived genetic material during reverse transcription and can integrate into the genomes of larger, more complex DNA viruses. In contrast, RNA viruses were believed not to integrate into the host's genome under any circumstances. We found that illegitimate recombination between an exogenous nonretroviral RNA virus, lymphocytic choriomeningitis virus, and the endogenous intracisternal A-type particle (IAP) retrotransposon occurred and led to reverse transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
139
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(141 citation statements)
references
References 17 publications
0
139
0
2
Order By: Relevance
“…In addition, like LCMV, other retroelements may cause the integration of RNA viruses [57]. Although the mechanisms are still unclear, several other RNA viruses have been reported to be integrated into their host chromosomes [58][59][60][61][62].…”
Section: (B) Possible Novel Pathogenicity Of Borna Disease Virusmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, like LCMV, other retroelements may cause the integration of RNA viruses [57]. Although the mechanisms are still unclear, several other RNA viruses have been reported to be integrated into their host chromosomes [58][59][60][61][62].…”
Section: (B) Possible Novel Pathogenicity Of Borna Disease Virusmentioning
confidence: 99%
“…Therefore, RNA viruses have the potential for integration of virus-derived segments. Thus, analysis of integration events is important for understanding the pathogenicity of RNA viruses and virus vectors [51,57,95]. …”
Section: (B) Possible Novel Pathogenicity Of Borna Disease Virusmentioning
confidence: 99%
See 2 more Smart Citations
“…Another important property of bornaviruses was uncovered recently by an international team of researchers (Horie et al, 2010): BDV was shown to integrate a DNA copy of its mRNA into the genetic mat erial of the host in persistently infected cells. Although other non-retroviral RNA viruses are known to produce DNA versions of their genomes during replication (Klenerman et al, 1997;Geuking et al, 2009), borna viruses are so far unique in having left endogenous fragments of themselves in the genomes of many mammalian species, including humans (Horie et al, 2010). At least four copies of these elements-homologous to the BDV nucleoprotein and thus named endogenous Borna-like nucleo protein (EBLN)-have been found in the human genome, and their orthologues in the genomes of other primates.…”
mentioning
confidence: 99%